The Influence of Social Media-Based Occupational Safety and Health Promotion on Personal Protective Equipment Compliance among Online Drivers - Vania Karen Octaviani Munthe; Keleng Ate Ginting; Delita Br Panjaitan (JURNAL KESMAS DAN GIZI (JKG), 2026)
This study aims to analyze the effect of Occupational Safety and Health (OSH) promotion through social media on Personal Protective Equipment (PPE) compliance among online drivers in Kota Medan. This research employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest method. A total of 30 respondents were selected using accidental sampling. Data were collected through questionnaires and observation, with intervention delivered via social media platforms such as TikTok and Instagram. The results showed that the mean PPE compliance score increased from 58.20 in the pretest to 74.60 in the posttest, with a difference of 16.40. The Paired Sample T-Test indicated a p-value of 0.000 (p < 0.05), demonstrating a significant effect of social media-based OSH promotion on PPE compliance. In conclusion, social media is effective as a tool for OSH promotion in improving safe behavior among online drivers. Therefore, social media utilization is recommended as an innovative strategy to enhance PPE compliance among informal sector workers.